Education Law and Policy in the Time of COVID-19: Using a Legal Framework to Expose Educational Inequity - Raquel Muñiz (SAGE Publishing, 2021)
Empirical data show that the COVID-19 pandemic deepened and exacerbated social inequalities, to the detriment of low-income communities of color. Using the law as a conceptual framework and legal research methodology, this study examines education law against the exacerbated social inequalities low-income students of color faced during the pandemic. Considering the bounds of the law against the exacerbated social inequalities surfaces the limitations of the law in a time of large-scale crisis and thereby exposes issues of educational inequity. In this context, policymakers bear the responsibility to adopt policies that promote educational equity. The study brings educational law and policy issues in the COVID-19 context to the fore of the educational equity discourse within the educational research community and has implications for policy and practice as well. The study is of import as educational researchers continue to examine the impact of COVID-19 across numerous social contexts and disciplines.